2009
DOI: 10.1557/jmr.2009.0414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sample geometry on deformation modes of bulk metallic glasses at the nano/micrometer scale

Abstract: Intense debates have been prompted concerning whether homogeneous deformation can be achieved in bulk metallic glasses at room temperature through the suppression of shear bands at the submicron scale. In this short communication, we demonstrate that multiple shear banding can be successfully attained via a proper modification of the microsample geometry, resulting in the appearance of a homogeneous deformation mode at the submicron scale. However, the apparent deformation homogeneity in our microcompression e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Before proceeding, we would like to further discuss the physical meaning of shear band initiation and the length scale we extracted. According to the prior experimental 10,11,40,[42][43][44] and computational 9,47 results, shear band initiation was usually associated with the transition from a homogeneous deformation to inhomogeneous (shear-banding) deformation in a uniaxial test, either tension or compression, with the transition size ranging from $100 nm to $400 nm. However, there were also experimental reports that shear banding still prevailed at the length scale of $100 nm; 41,48-51 the recent computational simulation 9,47 even showed that shear banding can be observed down to the length scale of 10 nm.…”
Section: Resultsmentioning
confidence: 96%
“…Before proceeding, we would like to further discuss the physical meaning of shear band initiation and the length scale we extracted. According to the prior experimental 10,11,40,[42][43][44] and computational 9,47 results, shear band initiation was usually associated with the transition from a homogeneous deformation to inhomogeneous (shear-banding) deformation in a uniaxial test, either tension or compression, with the transition size ranging from $100 nm to $400 nm. However, there were also experimental reports that shear banding still prevailed at the length scale of $100 nm; 41,48-51 the recent computational simulation 9,47 even showed that shear banding can be observed down to the length scale of 10 nm.…”
Section: Resultsmentioning
confidence: 96%